Informality, Employment and Economic Development in the Arab World - Elbadawi, Ibrahim; Loayza, Norman (2012)
This paper studies the causes and consequences of informality and applies the analysis to Arab countries. It starts with a review of employment, labor informality and other labor market outcomes in the Arab world; and a discussion on the definition and measures of informality, as well as on the reasons why widespread informality should be of great concern. The paper also analyzes informality's main determinants, arguing that informality is not single-caused but results from the combination of poor public services, a burdensome regulatory regime, and weak monitoring and enforcement capacity by the state. This combination is especially explosive when the country suffers from low educational achievement and features demographic pressures and primary production structures. Finally, using cross-country regression analysis, the paper evaluates the empirical relevance of each determinant of informality. It then applies the estimated relationships to several Arab countries to assess the country-specific relevance of each proposed mechanism. Results suggest that informality has had negative marginal effects for Micro and Small Enterprises' (MSEs') performance in the Arab world. Moreover, informal establishments might have difficulty penetrating regional or international markets; instead, they are likely to specialize in producing for local markets.